Concept design of the megawatt power level gyrotron stabilized by a low-power signal for DEMO project. (28th January 2022) - Denisov, Gregory; Kuftin, Andrey; Manuilov, Vladimir; Chirkov, Alexey; Popov, Leonid; Zapevalov, Vladimir; Zuev, Andrey; Sedov, Anton; Zheleznov, Ilya; Glyavin, Mikhail
Abstract: The specific features of the main components of the new powerful 230 GHz/80 kV/40 A gyrotron aimed to use in the future control fusion facility DEMO are described. The gyrotron design provides a stable output power generation of more than 1 MW using a superconducting magnet with a moderate size warm bore. Furthermore, the new original quasi-optical converter providing the gyrotron operation in three possible regimes—two free oscillation regimes with co-rotating TE33, 13 or counter-rotating TE33, −13 mode, and the regime with frequency locking by the stable input signal—is suggested and optimized. The Gaussian content in the output wave-beam in all above-mentioned regimes is about 98%.